2016
DOI: 10.1371/journal.pone.0152918
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epigenetic Biomarkers of Lung Adenocarcinoma through Multi-Omics Data Analysis

Abstract: Epigenetic mechanisms such as DNA methylation or histone modifications are essential for the regulation of gene expression and development of tissues. Alteration of epigenetic modifications can be used as an epigenetic biomarker for diagnosis and as promising targets for epigenetic therapy. A recent study explored cancer-cell specific epigenetic biomarkers by examining different types of epigenetic modifications simultaneously. However, it was based on microarrays and reported biomarkers that were also present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…Enhanced H3K4me3 was con rmed in lung cancer 12,13 , which was attributed to upregulated SETD1A, owing to no differences in other histone methylases between lung cancer tissues and adjacent nontumor tissues (FIGURE S5). However, the downstream effects of SETD1A are different in different tumors.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Enhanced H3K4me3 was con rmed in lung cancer 12,13 , which was attributed to upregulated SETD1A, owing to no differences in other histone methylases between lung cancer tissues and adjacent nontumor tissues (FIGURE S5). However, the downstream effects of SETD1A are different in different tumors.…”
Section: Discussionmentioning
confidence: 96%
“…SETD1A is an important methyltransferase to catalyze H3K4me3. Because more H3K4me3 was present in lung cancer cell lines 12,13 , we monitored the level of H3K4me3 in SETD1A knockdown A549 cells. Immuno uorescence showed that SETD1A silencing resulted in an obvious signal reduction of H3K4me3 in the global nucleus (FIGURE 5A-B).…”
Section: Setd1a Regulates Oncogene Expression In Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…51 This findings suggest the importance of the three main epigenetic mechanisms, DNA methylation, histone code modifications and chromatin remodeling complexes in cancer progression (table I and II). [52][53][54][55][56][57][58] Along with, overexpression of BRG1 and BRM in the cisplatin toxicity, 50 or doxorubicin chemo resistance mechanisms associated with the expression of the subunits SMARCB1 and SMARCA4 (BRG1) in front to NSCLC cells. 51 All of that, suggesting the importance of the three main epigenetic mechanisms DNA methylation, histone code modifications and chromatin remodeling complexes in cancer progression and potential new oncological therapeutic strategies in NSCLC, all of which have been shown in…”
Section: Epigenetics Therapeutics In Nsclcmentioning
confidence: 99%